2009
DOI: 10.1021/es901276e
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Controls on the Corrosion of Depleted Uranium Alloy in Subsurface Soils

Abstract: Military activities have left a legacy of depleted uranium (DU) penetrator waste in the near-surface terrestrial environment. To understand the fate of this DU alloy, the mechanisms and controlling factors of corrosion need to be determined. In this study, field-moist and waterlogged microcosms were used to investigate the effect of redox conditions and soil water content on the corrosion and fate of DU in subsurface soil, and the impact of corroding DU on the soil microbial population. The mechanism of corros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 20 publications
2
19
0
8
Order By: Relevance
“…3 Using the size information on penetrators reported by Bleise et al, 2 it is roughly estimated that the corrosion rate of the "HP" and "Hz" penetrators is 0.22 ± 0.05 and 0.26 ± 0.05 g cm −2 yr −1 , respectively (Table S2). These values fall in the range of the corrosion rates reported in laboratory column 19 and microcosm 16,18 studies with unsaturated soils (0.1−0.5 g cm…”
Section: Environmental Science and Technologysupporting
confidence: 52%
See 1 more Smart Citation
“…3 Using the size information on penetrators reported by Bleise et al, 2 it is roughly estimated that the corrosion rate of the "HP" and "Hz" penetrators is 0.22 ± 0.05 and 0.26 ± 0.05 g cm −2 yr −1 , respectively (Table S2). These values fall in the range of the corrosion rates reported in laboratory column 19 and microcosm 16,18 studies with unsaturated soils (0.1−0.5 g cm…”
Section: Environmental Science and Technologysupporting
confidence: 52%
“…Other studies also investigated U mineralogy of corroded DU bulk metal. For example, in laboratory microcosms, DU metal coupons cut from penetrators corroded in sandy soil, 16 estuarine sediment 17 or silty-loam soil 18 for about 500 days. The results indicated that DU metal mainly corroded to metaschoepite in unsaturated sandy and silty-loam soils, whereas uraninite formed in suboxic/anoxic estuarine sediment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…S1 in the supplemental material. The pH of each growth medium, including those lacking added uranyl nitrate, was standardized through the addition of an equivalent amount of HNO 3 . Where indicated, the supernatant from cell cultures was collected by centrifugation at 20,000 ϫ g for 8 min and then filtered through a 0.22-m membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The membrane potential probe bis-(1,3-dibutylbarbituric acid) trimethine oxonol [DIBAC 4 (3)] (Molecular Probes, Inc.), which enters cells with depolarized membranes, and the dead cell stain propidium iodide ReadyProbes (PI) (Molecular Probes, Inc.) were used to assess cell viability during growth arrest induced by 350 M U(VI). DIBAC 4 (3) was added at 1 g/ml, and PI was used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation